the The Influence Of Tax Sanctions, Motivation, Socialization, And Implementation E-Filing On The Compliance Of UMKM Taxpayer : MSME Taxpayer Compliance, Tax Sanctions, Motivation, Socialization, Implementation of e-filing - khoirina farina (ADPEBI, 2024)
Taxes have a very important role in the Indonesian economy because taxes are the main source for the State of Indonesia to fund the State Budget (APBN). Factors that can be emphasized by the apparatus in increasing tax compliance are providing tax sanctions, motivation to pay taxes, and socializing tax regulations either through counseling, moral appeals either with media billboards, or billboards, or opening tax regulation sites that can be accessed by taxpayers at any time. Based on this, the research objective is to examine the effect of tax sanctions, tax motivation, socialization, and the application of e-filing on taxpayer compliance. This study uses a quantitative method with a random sampling method approach. Data collection technique through Questionnaire. The questionnaires were collected at Metro Tanah Abang Market and the respondents in this study were 110 people. The results showed that tax sanctions did not affect taxpayer compliance. Other variables, namely motivation, tax socialization, and the implementation of e-filing, have a positive and significant influence on MSME taxpayer compliance.